2013
DOI: 10.1038/jp.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium for newborns with hypoxic-ischemic encephalopathy: a systematic review and meta-analysis

Abstract: The improvement in short-term outcomes without significant increase in side effects indicate the need for further trials to determine if there are long-term benefits of magnesium and to confirm its safety. Mortality was statistically insignificant between the magnesium and the control groups. However, the trend toward increase in mortality in the magnesium group is a major clinical concern and should be monitored closely in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 33 publications
5
37
2
3
Order By: Relevance
“…In addition, posttreatment of newborn piglets did not show any beneficial changes in the severity of the delayed energy failure as measured with cerebral PCr/Pi, NTP/exchangeable phosphate pool (EPP), or Lac/Cr and NAA/Cr [48] . These MRS results complement the discrepant findings regarding magnesium, in terms of histopathological and neurodevelopmental outcome measures, in both preclinical [49] and clinical studies [50] . Xenon, another NMDA receptor antagonist, is used as a gaseous anesthetic.…”
Section: Reduction Of Glutamate Excitotoxicity and Maintenance Of Calsupporting
confidence: 54%
“…In addition, posttreatment of newborn piglets did not show any beneficial changes in the severity of the delayed energy failure as measured with cerebral PCr/Pi, NTP/exchangeable phosphate pool (EPP), or Lac/Cr and NAA/Cr [48] . These MRS results complement the discrepant findings regarding magnesium, in terms of histopathological and neurodevelopmental outcome measures, in both preclinical [49] and clinical studies [50] . Xenon, another NMDA receptor antagonist, is used as a gaseous anesthetic.…”
Section: Reduction Of Glutamate Excitotoxicity and Maintenance Of Calsupporting
confidence: 54%
“…There were no cases of ‘clinical hypermagnesemia’ related to treatment overdosing (almost exclusively in patients with renal dysfunction). Therefore, MgSO 4 appears to present an optimal safety profile .…”
Section: Therapeutic Index and Cost‐effectivenessmentioning
confidence: 97%
“…There were no cases of 'clinical hypermagnesemia' related to treatment overdosing (almost exclusively in patients with renal dysfunction). Therefore, MgSO 4 appears to present an optimal safety profile (2,5,(17)(18)(19)(20)31,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)48,49,59,(68)(69)(70)(71)(72).…”
Section: Therapeutic Index and Cost-effectivenessmentioning
confidence: 99%
“…While as an individual treatment, magnesium has shown efficacy in experimental brain injury models including perinatal asphyxia, stroke, subarachnoid hemorrhage (SAH) and traumatic brain injury (TBI), results of clinical trials for these disorders have been generally disappointing, showing little or no effect. Despite this, in a recent perinatal asphyxia meta-analysis study, it was concluded that magnesium therapy led to improvements in shortterm outcomes and was relatively safe, although there was a trend for increased mortality [4]. More importantly, drawing on our own findings, our laboratory has shown that combined mild hypothermia (35°C) and magnesium treatment has synergistic neuroprotective effects and reduces brain injury when administered several hours after global and focal cerebral ischemia [2].…”
mentioning
confidence: 96%